Organizational Culture And Knowledge Management: A Study Of Dangote Cement Manufacturing Firms, Obajana, Kogi State, Nigeria - Ojochide, Icheme Monday; Julius A., Ikharehon; Joy, Itoya (International Journal of Scientific Research and Management (IJSRM), 2018)
The objective of the study was to ascertain the role of organizational culture in knowledge management with particular reference to Obajana Cement Manufacturing Firms, Kogi State. The study employed secondary data mainly through the reviewed literature Findings revealed that supportive culture and innovative culture significantly influence knowledge sharing and knowledge creation while bureaucratic culture at times affects knowledge acquisition to some extent. The bureaucratic culture at times affects knowledge acquisition to some extent. Bureaucratic culture can be effective depending on the situation and work environment. The study concluded that organizational culture (Bureaucratic, supportive and innovative culture) strongly determines the extent to which knowledge management is implemented in the organization. Organization culture is a strong predictor of knowledge management, its success or failure to enhance the organization's sustained competitive advantage toward better performance. The study finally recommended that organizations will endeavor to adopt a bureaucratic culture as it tends to create the expectation among organizational members and influence management to provide a clear vision of purpose for knowledge management before the employees will embark on the implementation of knowledge management activities. Although supportive culture and innovative culture help organizations to meet up the demands and needs of customers through knowledge creation, acquisition, and sharing. Organization members should be re-oriented based on the essence of new knowledge to facilitate their job performance